Factors Affecting Distribution of Oil Products in Kenya: A Case Study of Kenya Pipeline - Wawuda, Shigadi Miriam; Mungai, Dr Faith (International Journal of Supply Chain Management, 2016)
Purpose: The study was on the challenges facing the distribution of oil product through the Kenya Pipeline. It aimed to establish the effect of pilferage on distribution of the oil products in Kenya, to determine the effect of infrastructure on distribution of the oil products in Kenya, to find out the effect of capacity on distribution of the oil products in Kenya and to determine the effect of Information Technology on distribution of the oil products in Kenya. The biggest beneficiary to this study may be the Kenya Pipeline. Methodology: A descriptive case study design was appropriate for this study. The researcher used a self administered or self report questionnaire as a data collection tool. The questionnaire contained both open ended and close ended questions. The data was analyzed by use of descriptive statistics such as means and percentages. The data was then presented using graphs, charts and tables. Results: On Pilferage 100% respondents agreed that it affects distribution of oil in Kenya. Forty one percent (41%) respondents agreed that the road infrastructure affects distribution of oil products in Kenya while the smaller group (13%) stated they did not think the road infrastructure did affect distribution of oil. Majority respondents (45%) agreed that capacity affects distribution of oil products in Kenya while 9% disagreed to capacity affecting distribution of oil products in Kenya. On Information Technology and its effects on distribution of oil products in Kenya, majority (37%) stated that Information Technology does not affect distribution of oil while 17% agreed it does affect oil distribution. Unique contribution to theory, practice and policy: The study recommended that measures should be taken in order to safeguard against pilferage and improve oil distribution in Kenya; infrastructure should be well maintained while Capacity has a need to be increased. As for Information Technology it should be improved so as to meet the ever changing technological needs.